Urban acupuncture: Strategic design for campus street furniture based on generation Z preferences - Fitriyanto, Dominikus Aditya; Zakariya, Afif Fajar (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The end of the COVID-19 pandemic marks the beginning of a new era in many disciplines, including education. Campus life is starting to flourish, and there has been a significant increase in the use of public spaces, but this has not been accompanied by the renewal and improvement of the campus public spaces that students frequently use for studying and other activities. Many of the street furniture was in poor condition, uncomfortable to use, or could not serve the users. This study aims to define the ideal public space from the perspective of Generation Z students as the users. To collect data, a closed questionnaire is distributed to students from various adjacent faculties. The information is then quantitatively processed to obtain the preferences of street furniture through several parameters, including shape, color, and material. According to the analysis, the best campus street furniture has a circular or face-to-face shape, is geometrically balanced, uses bright, natural colors, and has natural expression. Other improvements include adding more furniture, adding power or electricity, and adding shading. The conclusions of this conversation can act as an outline of guidelines for administrators and stakeholders on campus when planning public spaces and the elements that constitute them up to fulfill the needs of users.